Penetapan Usia Minimal Perkawinan dalam Undang-Undang Nomor 16 Tahun 2019 Perspektif Maqasid Syari’ah Kontemporer - Mariya Ulva; Barden Alfinurin Aufa Hikam (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The amendment of the minimum marriage age to 19 years for both men and women under Law Number 16 of 2019 reflects the state’s response to child marriage and its social impacts. This study examines the regulation through the lens of contemporary maqashid al-sharia as developed by Jasser Auda, using a normative juridical method with statutory and conceptual approaches. The findings show that the policy aligns with contemporary maqasid al-sharia, particularly in safeguarding and developing the soul, intellect, and lineage, and demonstrates a state legal ijtihad oriented toward public welfare and family sustainability.